Clinico-pathological Spectrum of Pyogenic Granuloma in Patients Presenting at Ayub Teaching Hospital, Abbottabad - Shabana Naz, Shagufta Naeem, Abdur Rehman, Zainab Jadoon, Naveed Khan, Ammar Bin Saad, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Oral Pyogenic Granuloma (OPG) is a type of oral mucosal lesion that is distinguished by its rapid development, friable nature, and vascular proliferation. Aim: To examine the demographic and histopathological features of patients diagnosed with oral pyogenic granuloma. Study design: The cross-sectional study. Methodology: This study was conducted in the Dentistry Department of Ayub Medical College, Abbottabad following the acquisition of a comprehensive medical history through a pre-established form, pertinent clinical information pertaining to the patients, including age and lesion location, was collected. All excisional biopsy specimens were collected. Following preservation in 10% neutral buffered formalin, the gathered specimens underwent preparation for paraffin embedding. The histopathological findings that were assessed and documented included the observation of ulceration, inflammatory cell infiltration, vascular proliferation, fibrosis, and epithelial alterations. Data was analyzed in SPSS. Results: The 51 patients who were a part of the research had a mean age of 31.14+SD and were all female. The bulk of the patients were between the ages of 26 and 35. Lesion diameters varied from 0.5 to 3 cm, with 1.1 to 2 cm being the most common size range. 78% of the cases involved pregnant females. The most common site was the gum mucosa, lips, tongue, and palate were the next most typical locations for OPG. The majority of patients had pseudoepitheliomatous hyperplasia, mild chronic inflammation, and fibrosis, in addition to lobules of capillary sized blood vessels according to histopathological examination. Conclusion: Oral Pyogenic Granuloma is predominantly seen in young females, and is mostly associated with pregnancy and most common site is gum mucosa. The histopathological findings demonstrate characteristic features such as pseudoepitheliomatous hyperplasia, chronic inflammation, and fibrosis. Understanding these features contributes to accurate diagnosis and management of this lesion. Keywords: Oral Pyogenic Granuloma, lobular capillary hemangioma, pseudoepitheliomatous hyperplasia.